Implementation of Sharia Risk Management in Handling Problematic Musyarakah Financing at Baitul Maal Wat Tamwil (BMT) - Cahya Maharani; Dina Hanifah Masri; Rahmah Dhani (Business Finence Analyst Co.,, 2025)
This article analyzes the role of Baitul Mal Wat Tamwil (BMT) as a non-bank microfinance institution that operates based on sharia principles with a profit-sharing system, which aims to improve the economic welfare of small communities. BMT provides financing products with the Musyarakah principle to support the sustainability of community businesses, especially in the field of Micro, Small and Medium Enterprises (MSMEs). However, despite its significant benefits, BMT also faces various risks that can affect its smooth operations. These risks are related to uncertainties that can lead to unexpected losses such as delays in financing payments. Therefore, the implementation of effective risk management is essential to mitigate these potential losses. Risk management includes the steps of planning, organizing, implementing, and controlling the risks that may occur. The method used in this research is the distribution of questionnaires directly to BMT officers using SmartPLS to analyze the relationship between the application of sharia risk management in handling problematic financing in BMT.This article discusses the importance of implementing good risk management in BMT to ensure smooth operations and business sustainability in the midst of existing challenges. Through this approach, it is expected that BMT can continue to operate optimally in improving the welfare of the community based on sharia principles. Keywords: Sharia risk management, Musyarakah financing, Baitul Maal wa Tamwil (BMT), internal conflict of interest, non-performing loans, agency theory.